INVESTIGATING INDONESIAN TEACHERS’ STRATEGIES OF TEACHING ENGLISH IN MIXED ABILITY CLASSES - Isry Laila Syathroh; Bachrudin - Musthafa; Pupung - Purnawarman (STKIP Siliwangi, 2019)
Mixed-ability Class (MAC) is often unavoidable in the practice of education. MAC usually consists of many students with very different characteristics, in terms of their ages, proficiency, motivations, educational backgrounds, learning styles, etc. Despite the abundant research about teachers’ strategies in teaching English in homogenous classes, research of teachers’ strategies in teaching MAC is relatively unexplored. This study investigated the teaching strategies used by 10 (ten) English teachers in Cimahi as the respondents. Questionnaire was used as the instrument. Using descriptive analysis, the result showed that most lecturers perceive that teaching English in MAC gives advantages as well as disadvantages. Most of them admit that MAC provides greater opportunity for teaching innovation and creativity so they can develop themselves professionally. They are challenged to adopt many problem solving approaches to the difficulties they face in the classroom. However, many of them still have problems in managing the class such as: controlling students’ discipline, maintaining students’ interests, conducting effective learning, error correction and selecting classroom materials. The implementation of teacher training program, classroom action research and students’ placement test are recommended to avoid very diverse MAC. Keywords: Mixed Ability Classes, English Foreign Language, Teacher Strategies